Dilema Keterwakilan Perempuan Sebagai Calon Anggota Legislatif PPP (Partai Persatuan Pembangunan) Di Kabupaten Lamongan Pada Pemilu Tahun 2024 - Ainiyah Mufidatun Maghfiroh; Alif Firdaus Zamzam; Halimur Rosyid; Mahmud Aprian Mabruri; Midkholus Surur (Madani: Jurnal Politik dan Sosial Kemasyarakatan, 2024)
Women's representation has not reached the 30 percent quota as people's representatives, although from year to year the trend is improving. The researcher chose the PPP party on the grounds that 40 percent of the candidates it carried were women, but all of them still did not succeed in being elected representatives. The objectives of this study are 1) To find out the representation of women as PPP legislative candidates. 2) To find out the obstacles and challenges in the implementation of the 30 percent quota provisions. This research method uses a qualitative method. The data collection technique uses interviews, observations, and documentation. The results of this study show that the high representation of women as legislative candidates in the 2024 election in the PPP party is only a fulfillment of the quota. The obstacles and challenges experienced by female candidates, namely, the relocation of constituencies, are only as a fulfillment of quotas for women's representation and the lack of a party budget.